The phenomenon of word-creation as a kind of language game (on the example of the online dictionary Slovodna) - Tsudikova, Daria (Vilnius University Open Series, 2024)
This study aims to investigate the implementation of the phenomenon of word creation as a kind of а language game in the modern media space – the social network Instagram. The theoretical part of the study is based on several works devoted to the phenomenon under study by Boris Norman, Vladimir Sannikov, Tatiana Kuranova, and Lidia Malygina. The basis of the practical part of the article was the analysis of examples from the Internet dictionary SlovoDna, aimed at comparing language game techniques with their direct implementation in the modern Russian language. Current work uses methods such as introspection and reconstruction of the internal form of wordplay and their word-forming analysis. As a result of the research, nonce words are singled out into several subgroups based on the method of formation (reception); the main functions of the word-formation language game implemented by the authors of the Internet dictionary while creating words are determined; conclusions about the linguistic experiments of SlovoDna are made.